PEMBERDAYAAN PEREMPUAN OLEH ORGANISASI AKAR RUMPUT (KASUS PERAN KOPERASI KELOMPOK PENGAJIAN DI DESA SRIWULAN KABUPATEN DEMAK) - Untari, Sri (Faculty of Social Science, Universitas Negeri Semarang, 2009)
This study shows that the empowerment of local women through the organization formed by theirÃ‚Â own efforts more effective than others who come from outside their community. The village is a villageÃ‚Â Sriwulan transition from traditional culture to modern culture. These changes are marked by the emergenceÃ‚Â of local institutions, namely the organization of grass-roots organizations (grassroots organizations) areÃ‚Â diverse and have an important role in community empowerment. Local institutions appear on the initiativeÃ‚Â of the community and have a real agenda to strengthen the public welfare efforts. An important found roleÃ‚Â in this research is a study group of mothers who do womenÃ¢â‚¬â„¢s empowerment activities of its members,Ã‚Â not just on matters of religion, but also social issues, economics, and art.Keywords: Empowerment of women, the organization of grass-roots